Design and Development of a Micro-Hydro Vortex Turbine Prototype with Cylindrical and Conical Basins Using a Hybrid Microcontroller-Based Solar Energy System for Renewable Energy Practicum at Politeknik Negeri Medan - Idham Kamil; Al Qadry; Darwis A.R; Mardiana Mardiana (Journal of Innovative and Creativity, 2026)
This study aims to design and develop a prototype of a micro-hydro vortex turbine featuring two geometric variations—cylindrical and conical basins—as a practicum tool for the Renewable Energy course at Politeknik Negeri Medan. The system is equipped with a microcontroller-based digital control unit to monitor real-time water discharge, and it utilizes solar energy as the primary power source. The research adopts an engineering experimental approach, encompassing the design, fabrication, hydraulic performance testing, and integration of the monitoring system. The expected outcomes include a functional prototype, an integrated monitoring method, comparative performance data for different turbine geometries, and educational outputs such as practicum modules and instructional videos. These findings are anticipated to contribute to the advancement of laboratory-scale renewable energy technologies and serve as an interactive educational medium in vocational micro-hydro learning systems.